ФАКТОРЫ РАЗВИТИЯ СОЦИАЛЬНО-КУЛЬТУРНОЙ КОМПЕТЕНЦИИ У БУДУЩИХ УЧИТЕЛЕЙ АНГЛИЙСКОГО ЯЗЫКА: К ВОПРОСУ ИССЛЕДОВАНИЯ ПРОБЛЕМЫ - Абдимуратова, Н. (SCIENCE and SOCIETY, 2017)
The article deals with the factors of socio-cultural competence of future English teachers’ methodological social-meaningful psychological pedagogical and culturological. The methodical basis of the research is psychological-pedagogical and didactic principles of teaching.
Keywords: socio-cultural competence; psychology; pedagogics; methodology; technology; form; methods